Implementation of an online emergency education programme at a public university in Mexico - González Barranco, Patricia; Balderas Rentería, Isaías; Esquivel Ferriño, Patricia Cristina; Gracia Vásquez, Yolanda Araceli; Vásquez Farías, E.E
The Universidad Autónoma de Nuevo León (UANL) is a large public university situated in Monterrey, Mexico. Most of the programmes, including a pharmacy related programme (Químico Farmacéutico Biólogo/Chemist Pharmacist Biologist), were running at the university until the pandemic. A lockdown was put in place where it was established that schools and non-essential jobs should be carried out from home. Since then, the UANL has started a training effort to migrate all current classes to online emergency educational schemes. Microsoft Teams was designated as the main platform. Students and faculty members were trained in its use and, after one month, classes were successfully restarted on this platform. The chosen platform was used to create virtual classrooms, problem-based learning was encouraged, and videos and discussion panels were used especially in place of pre-COVID-19 planned laboratory classes. The semester ended with good results, but faculty member training continues and the adaptation to a better organised online programme is now running. Options to try to compensate the lack of in person laboratory classes are still being explored.